2005
DOI: 10.1002/uog.1857
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cerebral ventriculomegaly: outcome in 176 cases

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
232
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(271 citation statements)
references
References 17 publications
31
232
3
5
Order By: Relevance
“…Malformations are more often found in cases of severe VM (Romero et al, 1988;Den Hollander et al, 1998). We have recently reported that 60% of 60 severe VM had an associated anomaly, the most common ones being ACC and spina bifida; however, non-CNS malformations accounted for almost 1/3 of detected anomalies (Gaglioti et al, 2005). Two other recent studies report on the outcomes of severe VM: Breeze et al (2007) found that 65% of the cases (13/20) had associated malformations, almost half of them being ACC.…”
Section: Structural Malformationsmentioning
confidence: 96%
See 4 more Smart Citations
“…Malformations are more often found in cases of severe VM (Romero et al, 1988;Den Hollander et al, 1998). We have recently reported that 60% of 60 severe VM had an associated anomaly, the most common ones being ACC and spina bifida; however, non-CNS malformations accounted for almost 1/3 of detected anomalies (Gaglioti et al, 2005). Two other recent studies report on the outcomes of severe VM: Breeze et al (2007) found that 65% of the cases (13/20) had associated malformations, almost half of them being ACC.…”
Section: Structural Malformationsmentioning
confidence: 96%
“…The low sensitivity before 24 weeks probably reflects the natural history of the disease, and not a measurement error, because severe VM is easily detectable, even on a qualitative basis: CSF accumulates in the ventricular system over time and VM becomes evident only later in gestation. In a recent study, only 57% of 60 cases of severe VM were diagnosed before 24 weeks of gestational age (Gaglioti et al, 2005). Diagnostic accuracy is affected by measurement variability.…”
Section: Investigation and Findingsmentioning
confidence: 98%
See 3 more Smart Citations